Non-Hodgkin's Lymphomas in Greece according to the WHO classification of lymphoid neoplasms a retrospective analysis of 810 cases - Economopoulos, T.; Papageorgiou, S.; Dimopoulos, M.A.; N. Pavlidis; Tsatalas, C.; Symeonidis, A.; Foudoulakis, A.; Pectasides, D.; Rontogianni, D.; Rizos, E.; Chalkia, P.; Anagnostopoulos, A.; et al. (Acta Haematologica, 2005)
The purpose of this retrospective study, the largest unselected series in our country, was to illustrate the clinicopathological features of non-Hodgkin's lymphoma (NHL) classified according to the World Health Organization (WHO) classification of lymphoid neoplasms. A retrospective analysis was conducted and clinical features of histological subtypes were established in 810 patients (age ≥ 15 years) with NHL who were treated at 8 major centers representative of Greece. There were 435 males and 375 females 95% of them aged >30 years. B symptoms were present in 34% of the patients, while 45.3% had stages I-II and 54.6% had stages III-IV. LDH was increased in 37% of the patients. B cell lymphomas formed 88% of the cases whereas T cell lymphomas formed 12% of the total. Indolent lymphomas accounted for 31.1%, aggressive ones for 66.7% and very aggressive ones for 2.4% of all NHLs. Among indolent lymphomas extranodal ones (MALT B cell lymphoma) were the most common subset while follicular lymphoma grade I and II and small lymphocytic ones presented with equal frequency. Among the aggressive lymphomas diffuse large cell lymphoma (DLCL) was the most common subtype; this entity along with large-cell immunoblastic lymphomas accounted for 45.2% of all B cell lymphomas. Among the T cell lymphomas, peripheral T cell lymphomas and anaplastic large cell lymphomas of the T/null-cell type were the most common subtypes. The most common extranodal presentation was the gastrointestinal tract (GI). Next in frequency were primary extranodal NHL of the head and neck region. MALT B cell lymphomas were found in almost half of the patients with GI tract NHL, whereas in all other extranodal places DLCL was the predominant histological subtype. The median survival for indolent and aggressive NHL was 123.5 and 55.5 months, respectively. This is the first report of a large series of malignant lymphomas in Greece using the WHO classification. It appears that there are no significant differences between NHL in Greece and other large series as far as clinical and extranodal presentation is concerned. The frequency of follicular lymphoma in the current study is comparable to that reported from Asian countries and mainland Europe, but lower than that of US and Northern European series. There were no important differences in the incidence of the remaining histological subtypes between Greece and other European countries. Copyright © 2005 S. Karger AG.
Keywords: Greece; Non-hodgkin's lymphoma; Who classification